(untitled) (Journal of Computational Mathematics, 2000)
In this paper we apply an approach introduced in [6] [7], where continuous norms and high order estimates and extension are used, to study the convergence of vortex methods for the 3-D Euler equations in bounded domains as the initial vorticity w_0 and the curl of the body force f are non-compactly supported functions. Convergence results are proved.